Comparative pharmacokinetics of two extended half‐life FVIII concentrates (Eloctate and Adynovate) in adolescents with hemophilia A: Is there a difference?. (2nd June 2019) - Carcao, Manuel D.; Chelle, Pierre; Clarke, Emily; Kim, Lussia; Tiseo, Laura; Morfini, Massimo; Hossain, Taneya; Rand, Margaret L.; Brown, Christine; Edginton, Andrea N.; Lillicrap, David; Iorio, Alfonso; et al.
Abstract: Essentials The PK parameters of Eloctate vs Adynovate were compared using one‐stage and chromogenic assays in 25 boys (12‐18 years). The FVIII levels were taken at 3, 24, 48, and 72 hours following a dose of either FVIII; levels analyzed by WAPPS PK program. The PK profiles (half‐life, clearance, and time to 5%, 3%, and 1%) were not statistically different for the two EHL FVIIIs. The significant interpatient variability in PK is mainly related to VWF levels (and blood group). Background: A head‐to‐head comparison of the pharmokinetcs (PK) of extended half‐life (EHL) factor VIII (FVIII) concentrates in the same subjects has not been reported. Recently, boys (ages 12‐18 years) with hemophilia A in Canada were required to switch from Eloctate to Adynovate. Objectives: Compare the PK profiles of Eloctate vs Adynovate in the same boys. Methods: Boys switching from Eloctate to Adynovate prophylaxis had FVIII levels sampled at 3, 24, 48, and 72 hours following a regular prophylactic infusion of Eloctate and then 1‐3 months later, of Adynovate. Testing was done by one‐stage assay (OSA) and chromogenic assay (CA). The PK parameters were determined with the Web Accessible Population Pharmacokinetic Service (WAPPS)–Hemo PK tool. Results: Twenty‐five boys (mean age 15.3 years; range: 12.1‐18.4; 9 O blood group) underwent switching. Mean (range) terminal half‐lives with the OSA were 16.1 hours (10.4 to 23.4; Eloctate) and 16.7 hours (11.0 to 23.6; Adynovate) (NS). With the CA, these were 18.0 hours (12.0 to 25.5; Eloctate) and 16.0 hours (10.3 to 22.9; Adynovate) ( P  = 0.001). There were no significant differences between the two EHL‐FVIIIs in clearance, area under the concentration vs time curve (AUC), Vss, or time for FVIII levels to drop to 5%, 3%, and 1%. At the 72‐h time point, mean observed FVIII levels following a mean dose of 39.3 IU/kg of Eloctate were 4.4% (OSA) and 4.4% (CA). For Adynovate, these were 5.1% (OSA) and 5.3% (CA) following similar doses. There was considerable interpatient variation in PK, mainly explained by differences in blood group/von Willebrand factor (VWF) levels. Conclusions: Eloctate and Adynovate have almost identical PK parameters. When switching from one to another no prophylaxis regimen change is needed.